Looking for lover Intertextual Studies of Song of Songs 3:1-5 and Fake Address Songs - Jusuf Haries Kelelufna (ADI Publisher, 2020)
The Song of Songs 3:1-5 and the 'fake Address' song sung by Ayu Ting Ting both speak of the search for a lover by a woman. This theme can be found in all love poems which later became the basis of all human search. The problem in both texts is the search that is not in accordance with social norms in society and the absence of spiritual aspects. The method in this research is an intertextual study by analyzing the contents and structure of the two texts. The results of the analysis revealed several aspects of the search; the search is carried out intensively, the search is driven by love born from the heart, the search goes beyond the norm in the eyes of the people, and the search involves God.